Epidural Anesthesia with Eissenmenger Syndrome Undergoing Caesarean Section : a Case Report - Kurnia, Fentti selli; Natapraja, Tresna Kusumah (Journal of Society Medicine, 2024)
Introduction: Heart disease in pregnant women can cause both morbidity and mortality. Eissenmenger syndrome is a pulmonary hypertension due to high pulmonary vascular resistance with a right-to-left or bidirectional shunt at the aortopulmonary, ventricular, or atrial level. To prevent hemodynamic instability and hypoxemia, it is essential to maintain a balance between PVR and SVR. Case Report: We reported the case of a 28-year-old pregnant woman with a gestational age of 34-35 weeks, diagnosed with Eissenmenger syndrome due to shortness of breath and cyanosis in the extremities, classified as ASA III E. After epidural anesthesia was administered, a 1.5 hour cesarean section was performed and a male baby was born. Postoperatively, the patient was transferred to the ICU. Conclusion: This case highlights the importance of maintaining a balance SVR and PVR, and continuous monitoring in pregnancy patient complicated by Eissenmenger syndrome. It requires a multidisciplinary approach involving obstetricians, anesthesiologists, and pediatricians.